In the shadow of National Socialism : early emigration and suicide of the oral pathologist Rudolf Kronfeld - Reinecke, Katharina (Pathology, research and practice, 2019)
The physician Rudolf Kronfeld (1901–1940) is undoubtedly one of the pioneering and most influential representatives of modern histopathology and oral pathology. Already at a young age he became a protagonist of the renowned, internationally leading “Vienna School”. Kronfeld’s outstanding professional significance stands in a peculiar contrast to the research situation to date: His curriculum vitae, but also his family background – and here in particular the fate of his family members in the Third Reich – have received little attention so far. Thus, the present study attempts to shed light on Kronfeld’s life and work and, in particular, the complex implications of his Jewish background. It is based on archival sources and a systematic re-analysis of the relevant specialist literature. The analysis demonstrates that Kronfeld’s early emigration was driven in part by the anti-Semitism that was tangible in Vienna in the 1920s. The last years of his life were considerably burdened by a serious illness and by repressive experiences which his Jewish family members and companions underwent after the “Anschluss” of Austria into Nazi Germany. Both essential events presumably contributed significantly to Kronfeld’s sudden suicide in 1940, at the height of his professional success.